Modeling of Reinforced Concrete Structures Under Cycling Loading - Mourlas, Christos (My University, 2016)
Modeling of reinforced concrete structures under seismic loading conditions is of significant importance especially when assessing this type of structures. The severe nonlinearities that are developed when reaching the ultimate limit state condition requires advanced numerical modeling through the use of stable and robust algorithms. This research work deals with the development of algorithms that will allow the modeling of severe nonlinearities during the cyclic loading of reinforced concrete structures. The software Reconan FEA is utilized where the cyclic loading solution algorithm is modified in order to allow for the capturing of the nonlinear cyclic response of reinforced concrete structures through 3D detailed modeling.
Keywords: Cyclic Loading; Reinforced Concrete Structures; Nonlinear Analysis; Material Model Development; Opening and Closing of Cracks; Smeared Crack Approach